Global methane pledge in Tajikistan: Assessment report - Malec, Karel; Babu, Suresh Chandra; Tohirzoda, Sino (International Food Policy Research Institute, 2024)
The Government of Tajikistan should consider joining the Global Methane Commitment as a strategic and prudent decision. Tajikistan's participation in the Global Methane Pledge offers numerous benefits that can positively impact the country's economy, environment, and global reputation. By joining this international effort to reduce methane emissions, Tajikistan can contribute to global climate change mitigation goals, demonstrating its commitment to addressing environmental challenges. This commitment becomes particularly significant for Tajikistan's agrarian economy, where sustainable livestock management practices can help reduce methane emissions from enteric fermentation, enhancing both environmental sustainability and agricultural efficiency. Additionally, the pledge emphasizes improved waste management and methane capture from solid waste sites, aligning with Tajikistan's green energy objectives, carbon market participation, revenue generation, and attracting international investments. Importantly, joining the Global Methane Pledge involves no legal obligations or penalties, offering Tajikistan a flexible and supportive framework for collaboration, knowledge sharing, funding access, and effective methane reduction measures implementation. Targeting main sources of methane emissions provides an opportunity to implement cost effective measures that yield multiple benefits, including improved air quality, reduced health risks from air pollution, enhanced energy efficiency, increased energy security, and the development of sustainable technologies and industries that foster economic growth and job creation. It is recommended that comprehensive studies be undertaken within each of the sub-sectors such as agriculture, energy, waste management and wastewater management. These studies will not only provide valuable insights to inform effective interventions, but also provide a basis for future re search and data-driven decision-making. It is also important to highlight that some measures can lead to cost avoidance in the long run. By focusing on mitigating methane emissions, Tajikistan can actively contribute to global climate change mitigation while reaping numerous positive out comes for its environment, public health, and economy. To determine the effects of measures, effective measurement is needed. Tajikistan has been improving the management and use of statistical data in recent decades as its Agency for Statistics under the President of the Republic of Tajikistan (TajStat) works closely with regional and international partners to improve data quality and reporting. However, the agency needs additional human and financial resources to support the collection of climate data and the development of indicators to monitor progress and to support sound policy decisions.